Prince of fire ebook - Silva, Daniel (Gabriel Allon, 2006)
#1 New York Times bestselling author Daniel Silva presents "a first-rate thriller" ( Rocky Mountain News ) featuring art restorer—and reluctant spy—Gabriel Allon. After an explosion in Rome destroys the Israeli embassy, Gabriel Allon makes a disturbing discovery—the existence of a dossier in terrorist hands that strips away his secrets, and lays bare his history. Drawn into the heart of a service he’d once forsaken, Allon finds himself stalking a master terrorist across a bloody landscape generations in the making. But soon, Allon will wonder who is stalking whom. When the final showdown comes, it won’t be Allon alone who is threatened with destruction. For it is not his history alone that has been exposed...